RETRACTED: Health risks and respiratory intake of submicron particles in the working environment: A case study - Gao, Xiangjing; Zou, Hua; Chen, Rui; Fang, Huanghong; Cao, Yiyao; Hu, Yong; Luan, Yuqing; Yuan, Weiming; Quan, Changjian; Zhou, Zanrong; Lou, Xiaoming; Zhou, Xingfan (Frontiers in Environmental Science, 2022)
Background: Powder-coating processes have been extensively used in various industries. The submicron particles generated during the powder-coating process in the workplace have complex compositions and can cause serious diseases. The purpose of this study was to better understand the health risks and respiratory intake of submicron particles during the powder coating process. Methods: The concentrations of and variations in submicron particles were measured using real-time instruments. The health risks of submicron particles were analyzed using the Stoffenmanager Nano model. A new computational fluid dynamics model was used to assess the respiratory intake of ultrafine particles (UFPs), which was indicated by the deposited dosage of UFPs in the olfactory area, nasal cavity, and lungs. The deposited doses of UFPs were used to calculate the average daily doses (ADDs) of workers, according to the method described by the Environmental Protection Agency. Results: The number concentration (NC), mass concentration, surface area concentration, personal NC, and lung-deposited surface area concentration of submicron particles were >105 pt/cm3, 0.2–0.4 mg/m3, 600–1200 μm2/cm3, 0.7–1.4 pt/cm3, and 100–700 μm2/cm3, respectively. The size distribution showed that the submicron particles mainly gathered between 30 and 200 nm. The health risk of submicron particles was high. Upon respiratory intake, most UFPs (111.5 mg) were inhaled into the lungs, a few UFPs (0.272 mg) were trapped in the nasal cavity, and a small minority of UFPs (0.292 mg) were deposited in the olfactory area. The ADD of male workers with 10 years of exposure in the olfactory area, nasal cavity, and lung were 1.192×10-3 mg/kg·d-1, 1.11×10-3 mg/kg·d-1, and 0.455 mg/kg·d-1, respectively. Conclusions: Owing to the high concentrations of submicron particles, the workers involved in the powder-coating process are at a high health risk. Moreover, the respiratory intake of UFPs by workers is high, which is suggested by the highly deposited dosage of UFPs in the lungs and the corresponding high ADD in workers. Control measures, including engineering control, management control, and personal protective equipment, must be improved for the protection of workers.